THU0181 SOLUBLE VASCULAR BIOMARKERS IN RHEUMATOID ARTHRITIS AND ANKYLOSING SPONDYLITIS: EFFECTS OF ONE-YEAR ANTI-TNF-Α THERAPY. (2nd June 2020) - Pusztai, A.; Hamar, A.; Horváth, Á.; Végh, E.; Bodnár, N.; Kerekes, G.; Czókolyová, M.; Szamosi, S.; Bodoki, L.; Hodosi, K.; Domjan, A.; Nagy, G.; et al.
Abstract : Background: Rheumatoid arthritis (RA) and ankylosing spondylitis (AS) have been associated with inflammatory atherosclerosis, increased cardiovascular (CV) morbidity and mortality. Numerous proteins may serve as biomarkers of inflammatory atherosclerosis. The treatment of arthritis by tumour necrosis factor α (TNF-α) inhibitors may decrease the serum concentrations of these biomarkers. Objectives: In this study we wished to determine circulating levels of oxidized LDL (oxLDL) - β2 glycoprotein I (β2GPI) complexes (AtherOx), anti-hsp60 antibodies, soluble urokinase plasminogen activator receptor (sUPAR) and N-terminal B-type natriuretic peptide (NT-proBNP) in sera of RA and AS patients. We also wished to assess the effects of anti-TNF treatment on these biomarkers. Methods: Altogether 53 arthritis patients including 36 RA patients treated with either etanercept (ETN) or certolizumab pegol (CZP) and 17 AS patients treated with ETN were included in a 12-month follow-up study.Circulating oxLDL/β2gpI complexes, anti-human Hsp60 immunoglobulin G (IgG) levels and BNP8-29 fragment levels were assessed by ELISA. suPAR levels were assessed by suPARnostic ® Quick Triage test. All laboratory assessments were performed at baseline, as well as 6 and 12 months after treatment initiation. Results were associated with DAS28, BASDAI, CRP. Results: In the mixed cohort of 53 arthritis patients, the circulating levels of oxLDL/β2gpI significantly decreased after 12 months of anti-TNF therapy (0.20±0.11 U/ml) compared to baseline (0.24±0.10 U/ml; p=0.014). There was a tendency of non-significant decrease after 6 months (0.23±0.14 U/ml) versus baseline. Anti-Hsp60 antibody levels did not change after 6 months (158.6±138.6 AU/ml) and 12 months (167.3±143.3 AU/ml) compared to baseline (170.3±140.4 AU/ml). Among the patients, 21.2% had low, 36.4% "observe", 9.1% high and 33.3% critical suPAR levels. suPAR levels showed a tendency of non-significant decrease after 6 months (11.3±17.7 ng/ml) and 12 months (10.3±15.3 ng/ml) versus baseline (11.5±16.4 ng/ml). However, when the four serum level categories described above were considered, suPAR concentrations exerted significant decrease in RA patients with critical suPAR levels (>9ng/ml) (p=0.04). Similarly, BNP fragment levels showed only a tendency of decrease after 6 months (518.2±422.4 pmol/l) and 12 months (484.1±418.2 pmol/l) versus baseline (530.8±441.8 pmol/l). However, serum BNP levels at baseline and after 12 months were significantly increased in CCP positive compared to CCP negative RA patients (baseline: 670.6±323.0 versus 138.0±436.4 pmol/l; p=0.030 and 12 months: 652.9±283.2 versus 456.5±423.1 pmol/l; p=0.021), as well as in RF positive compared to RF negative RA patients (baseline: 680.6±381.6 versus 292.9±198.3 pmol/l; p=0.007 and 12 months: 668.9±346.5 versus 312.2±207.0 pmol/l; p=0.001). Conclusion: One-year anti-TNF therapy significantly decreased circulating oxLDL/β2gpI complex levels. This therapy also decreased suPAR levels in patients with critically high suPAR. BNP fragment levels were associated with seropositivity in RA. These vascular biomarkers may reflect the effects of TNF inhibition on endothelial activation. Acknowledgments: This study was sponsored by an investigator-initiated grant from Pfizer. Disclosure of Interests: Anita Pusztai: None declared, Attila Hamar: None declared, Ágnes Horváth: None declared, Edit Végh: None declared, Nóra Bodnár: None declared, György Kerekes: None declared, Monika Czókolyová: None declared, Szilvia Szamosi: None declared, Levente Bodoki: None declared, Katalin Hodosi: None declared, Andrea Domjan: None declared, Gábor Nagy: None declared, Ibolya Szöllösi: None declared, Luis Lopez Employee of: Retired employee of Corgenix Inc., Eiji Matsuura: None declared, Zoltán Prohászka: None declared, Sándor Szántó: None declared, Zoltán Nagy: None declared, Yehuda Shoenfeld: None declared, Zoltán Szekanecz Grant/research support from: Pfizer, UCB, Consultant of: Sanofi, MSD, Abbvie, Pfizer, Roche, Novertis, Lilly, Gedeon Richter, Amgen, Gabriella Szücs: None declared